2009
DOI: 10.1380/ejssnt.2009.448
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bimetallic Au/Pd(110) Surfaces

Abstract: The growth as well as the compositional, electronic and structural properties of thin Au films deposited on a Pd(110) single crystal have been studied by means of ultraviolet photoelectron spectroscopy (UPS), photoemission of adsorbed xenon (PAX) and scanning tunneling microscopy (STM) as a function of film thickness (ranging from submonolayer amounts up to multilayers) and temperature. Our investigations indicate a Volmer-Weber growth mode of Au on Pd(110) at a deposition temperature of 300 K and below. As fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…There is also intensity around 6–7 eV. These bands around 2–5 and 6–7 eV correspond to the Au d bands and the flat region with a low intensity from E F to 2 eV corresponds to the Au s-p band as observed on Au surfaces and Au-rich Pd–Au surface alloys ( 24 26 ), indicating that the as-grown 2.4-ML Au/Pd(110) surface is similar to the Au surface. Therefore, the band around 2–3 eV near k y = 0 observed in Fig.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…There is also intensity around 6–7 eV. These bands around 2–5 and 6–7 eV correspond to the Au d bands and the flat region with a low intensity from E F to 2 eV corresponds to the Au s-p band as observed on Au surfaces and Au-rich Pd–Au surface alloys ( 24 26 ), indicating that the as-grown 2.4-ML Au/Pd(110) surface is similar to the Au surface. Therefore, the band around 2–3 eV near k y = 0 observed in Fig.…”
Section: Resultsmentioning
confidence: 92%
“…The amount of deposited Au atoms was monitored by a quartz oscillator placed near the sample. In the ARPES measurement, the amount of deposited Au was determined from the ARPES spectra on the basis of a previous study where the Au-derived band almost saturates in intensity at 1-ML Au ( 24 ). In the TDS experiments shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In the further discussion we will mainly concentrate on the most intense peak at 6.0 eV (peak A). Former studies by Salmeron et al [19] and Kobiela et al [20] on different Pt surfaces, by Moors et al [21] on Pd(110) and by Citrin and Wertheim [22] on a glass substrate showed that, independent of the used substrate, the position of this peak (stemming from the Au 5d 3/2 -derived subband) is stable at mono-and multilayer coverage. However, a characteristic shift to lower binding energy has been found for submonolayer coverages.…”
Section: Au On Pt(111)mentioning
confidence: 92%